Duration of suppression of bone turnover following treatment with zoledronic acid in men with metastatic castration-resistant prostate cancer. (20th October 2017) - Niraula, Saroj; Templeton, Arnoud J; Vera-Badillo, Francisco; Dodd, Anna; Nugent, Zoann; Joshua, Anthony M; Tannock, Ian F
Aim: Zoledronate is approved for use every 3 weeks in men with bone metastases from castrate-resistant prostate cancer (CRPC) but the basis for such frequency is unclear.Methods: In men with bone metastasis from CRPC we measured the markers of bone turnover - urine and serum telopeptides before the first injection of zoledronate and at four 3-weekly intervals thereafter. Men received further zoledronate treatment after 12 weeks, or earlier if the telopeptides did not meet predefined adequate suppression. The primary end point was the proportion of evaluable subjects with suppressed telopeptides at 12 weeks. Exploratory analyses evaluated predictors of bone turnover suppression and quality-of-life.Results: 31 patients were enrolled. Median age was 70 (range: 53–86) years. 65%, (95% CI: 46–81%) had suppressed telopeptides at 12 weeks. Prior skeletal-related events, chemotherapy, bone surgery and higher baseline levels of telopeptides were associated with shorter duration of telopeptides.Conclusion: 12-weekly zoledronate suppresses bone turnover in the majority of men with bone metastasis from CRPC. Lay abstract: Zoledronic acid (ZA) is a bone strengthening drug used for treatment of men with advanced prostate cancer in their bones. Based on initial clinical trials, ZA is approved for use every 3 weeks. However, recent clinical trials suggest similar outcomes when ZA is used every 12 weeks. In this clinical trial, we reaffirm that majority of men with prostate cancer only require every 12 weeks of ZA to achieve a reasonable biochemical response. Less frequent treatments may spare patients of the side effects, inconvenience and cost.